Heterogeneous digital stiffness programming. (August 2022) - Tao, Hongcheng; Danzi, Francesco; Silva, Christian E.; Gibert, James M.
Abstract: A heterogeneous design of mechanical metamaterial enables digital stiffness programmability. The prototype is composed of an elastomer matrix containing diamond-shaped cavities that are selectively confined along their diagonals by semi-rigid plastic beam inserts. Unit-cell perturbations caused by insert placement or removal reshape the global constitutive relation, whose lower and upper bounds correspond to configurations with all holes empty and all inserts in place, respectively, due to a gap between the elastomer and insert moduli. Bidirectional operation is accomplished by varying the orientation of the inserts, with longitudinal inserts increasing the macroscopic stiffness in compression and transverse inserts increasing that in tension. Arranged digital representations of such local insert states form the explicit encoding of global patterns, allowing both statical and in situ systematic stiffness programming with minimal mass changes. These properties establish a new paradigm for actively tuning vibration isolation systems in response to changes in the base structure's resonances.